Dependence on foreign raw materials - Franz -J. Jägeler (Intereconomics, 1974)
Being confronted with the oil crisis the dependency on foreign raw materials became worthwhile discussing again. Evaluations of certain raw materials indicate a low degree of self-sufficiency in some sectors. This article tries to give a general survey of the situation for the Federal Republic.
Keywords: 330; Germany